Modern Technologies in the Rehabilitation of Patients with Multiple Sclerosis and Their Potential Application in Times of COVID-19 - Ewa Zasadzka; Tomasz Trzmiel; Anna Pieczyńska; Katarzyna Hojan (Medicina, 2021)
Background and Objectives: The COVID-19 pandemic required the adoption of new technologies to improve access to healthcare at an unprecedented speed, as social distancing became mandatory. The aim of this systematic review was to analyze the effectiveness of using new technologies in the rehabilitation of multiple sclerosis (MS) patients and discuss their potential role during the COVID-19 pandemic. Material and Methods: The studies were identified by searching two online databases—PUBMED and Web of Science. Combinations of the key words “Multiple sclerosis” and “e-health”; “Multiple sclerosis” and “virtual reality”; “Multiple sclerosis” and “telerehabilitation”; “Multiple sclerosis” and “new technologies”; “Multiple sclerosis” and “tele-exercise” were used to find suitable publications. Results: A total of 17 studies were included. Although the overall number of participants in all the studies was 904, two of the studies were conducted on the same group. Thus, a total of 854 participants were involved in the studies included. All participants were diagnosed with MS. In 10 studies, participants had to be diagnosed according to the McDonald criteria. Of the included studies: five involved intervention at participants’ home, six were conducted using Xbox Kinect, and seven studies reported no adverse outcomes. Conclusion: The review proves telerehabilitation to be an effective motivational tool to restore and maintain both physical and cognitive function in patients with MS. Remote communication technologies seem to be measures of high effectiveness in rehabilitating and supporting MS patients especially during the COVID-19 pandemic, as the traditional rehabilitation option is less accessible or in some cases inaccessible for these patients.